KnowledgeBoat Logo

Mathematics

Prove the following :

cos θsin (90° - θ)+sin θcos (90° - θ)=2\dfrac{\text{cos θ}}{\text{sin (90° - θ)}} + \dfrac{\text{sin θ}}{\text{cos (90° - θ)}} = 2

Trigonometrical Ratios

11 Likes

Answer

To prove,

cos θsin (90° - θ)+sin θcos (90° - θ)=2\dfrac{\text{cos θ}}{\text{sin (90° - θ)}} + \dfrac{\text{sin θ}}{\text{cos (90° - θ)}} = 2

We know that,

sin (90 - θ) = cos θ and cos (90 - θ) = sin θ

Solving L.H.S. of the equation, we get :

cos θcos θ+sin θsin θ1+12.\Rightarrow \dfrac{\text{cos θ}}{\text{cos θ}} + \dfrac{\text{sin θ}}{\text{sin θ}} \\[1em] \Rightarrow 1 + 1 \\[1em] \Rightarrow 2.

Since, L.H.S. = R.H.S.

Hence, proved that cos θsin (90° - θ)+sin θcos (90° - θ)=2\dfrac{\text{cos θ}}{\text{sin (90° - θ)}} + \dfrac{\text{sin θ}}{\text{cos (90° - θ)}} = 2.

Answered By

5 Likes


Related Questions